Didactic Laws Methodological Basis of Modernization of the Educational Process - Shodmonova Zilola Bozorovna (Researchparks Publishing, 2022)
Mankind's centuries-old experience in building the state and society has led to the development of advanced approaches to the regulation of social relations on the basis of new approaches. The essence of these approaches in recent years has been expressed in general terms using the concept of